Calculation of Bed Occupancy Rate, Length of Stay, Turn Over Interval, Bed Turn Over On The Utilization of Beds In Fakhrudin Ward PKU Muhammadiyah Sruweng - Eva Mungawanah (Health Media, 2020)
This study aim to determine the results of the calculation of Bed Occupany Rate (BOR), Length Of Stay (LOS), Turn Over Interval (TOI), Bed Turn Over (BTO) on the use of beds in the Fakhrudin ward PKU Muhammadiyah Sruweg in 2018.The research method used was descriptive research with qualitative approach. The sampling technique used was saturated sampling, with inpatient recapitulation data sample of Fakhrudin ward in 2018.The results of the calculation of BOR, LOS, TOI and BTO on the Fakhrudin ward in the first quarter of 2018 shows the values of BOR ​​in the coverage of 74-88%, the values of LOS and TOI in 3-4 days and 0.5-1 days respectively,, and the values of BTO in 19-21 times. So it was concluded that the use of beds was quite high. Therefore, it is required to add or relocate beds / rooms to the ward so that the demand for beds for inpatients is fulfilled without patient care system.